THE ROLE OF THE STATE EXECUTIVE IN THE EXECUTIVE IN THE EXECUTION PROCESSES (World Bulletin of Management and Law, 2024)
The author examines the main problems of enforcement proceedings, primarily due to the high social significance of enforcement proceedings, its place and role in the Russian legal system,which has recently been subjected to radical reform. The issues of improving legislation on enforcement proceedings have been and are under the close attention of legislative, executive, judicial bodies, the scientific community and persons engaged in law enforcement activities.
Keywords: State executive; execution processes